(untitled) (Web of Teachers: Inderscience Research, 2023)
This article explores the role of synonymous words in the speech development of elementary school students. It investigates the significance of vocabulary expansion, cognitive development, age-appropriate pedagogy, contextual understanding, and the pragmatic use of synonyms in nurturing effective communication skills among young learners. By recognizing these critical aspects, educators can design innovative strategies that enhance elementary students’ language development, fostering articulate and confident communicators.